SINTESIS ALPHA-TERPINEOL DARI ALPHA-PINENE DENGAN MENARA DISTILASI REAKTIF - , Tya Indah Arifta; , Prof. Ir. Arief Budiman, MS.,D.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Alpha-terpineol is a product that used in perfume industry, in pharmaceutical as an anti-fungal and an insect repellent, disinfectant and others. Recently, Î±-terpineol are being studied further to be developed as anti-cancer compounds. Alpha-terpineol can be produced from turpentine, which is a non-timber forest products originating from pine tree (Pinus merkusii). Gum turpentine is distilled to obtain turpentine as distillate and gondorukem as bottom product.Turpentine obtained has a composition of 73.30% Î±-pinene, 13.71% carene, 5.19%, Î²-pinene, campene, limonene and others. Alpha-pinene 87.05% is obtained by distilling turpentine using a distillation column operated at vacuum pressures. Reactive distillation column is an equipment that can be operated as both a place of reactions and separation processes. Alpha-pinene and water react with catalyst (chloroacetic acid) in reactive distillation column at the vacuum pressure and total reflux. The variables studied in this research include optimum feed plate, pressure and the ratio of catalyst solution and solution of Î±-pinene to yield Î±-terpineol. The lower of feed plate will give lower Î±-terpineol yields. This is because the lower position of feed plate provide a shorter reaction zone. Hydration of Î±-pinene is an endothermic reaction. The increase in pressure causes the temperature rises and equilibrium reaction shifted towards the the product and the yield will be higher. Because of ÎP in this study is quite small (19, 20, 21, 22 and 23 inHg) causes relatively constant yield. The increasing of ratio of catalyst solution and solution of Î±-pinene accelerate the hydration and increase the amount of water as reactant. In fact, the conversion of Î±-pinene increased with the increasing of ratio of catalyst solution and Î±-pinene solution but selectivity of Î±-terpineol decreased. This is due to isomerization of Î±-pinene producing limonene and Î³-terpinene as byproducts. The two stages of the hydration of Î±-pinene into Î±-terpineol, which controls is the hydration of Î±-pinene into terpine hydrate, not dehydration of terpine hydrate to Î±-terpineol.